Pandemic legalities : legal responses to COVID-19 - justice and social responsibility - Cowan, David (David S.); Mumford, Ann (Bristol : Bristol University Press, 2021)
The effects of COVID-19 are visited disproportionately on the already disadvantaged. This text maps out ways in which those already disadvantaged have been affected by legal responses to COVID-19. Contributors tackle issues including virtual trials, adult social care, racism, tax and spending, education and more. They reflect on the implications of COVID-19, express concerns with policy and practice developments and the neutral version of the law and the economy which has taken root. Drawing on diverse resources, it offers an account of the damage caused by legal responses to the pandemic and demonstrates how the future response can be positive and productive.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 14, 2021).
Keywords: COVID-19 (Disease) -- Law and legislation; COVID-19 Pandemic, 2020- -- Government policy; Social justice; Law; Laws of specific jurisdictions & specific areas of law